Exploring Polytechnic Learners’ Perception on Multimodality in MALL in Business Administration Instruction - Rahmanu, I Wayan Eka Dian; Santosa, Made Hery (Dinamika Pendidikan, 2022)
This paper aimed to analyze Polytechnic learners’ perception of multimodality in Mobile-Assisted Language Learning (MALL) in an English instructional context. This research was a survey with a quantitative approach. Purposive sampling was employed and considered only for students who learned English language lessons at eight classes in the Business Administration Department, Politeknik Negeri Bali. Questionnaires focused on the Performance Expectancy (PE), Effort Expectancy (EE), and Behavior Intention (BI) of UTAUT theory. The result of the study indicated that internet technology was prevalent to be used by the students and there was a keen exploration of the English materials in a multimodal perspective that is a combination of technology-based learning materials with various modes, involving audiovisual, pictures, realia, in different formats. The usefulness of the device and the ease of technology used contribute to the use of mobile-assisted language learning (MALL) in learning the English language. The result also revealed the entrepreneur candidates tended to choose MALL with multimodal immersion as a fruitful combination to escalate their English language skills. Policies, subject matter expertise, appropriate pedagogies, and relevant use of technology support are suggested to explore the usefulness of MALL for students in Polytechnic education.